“We’ll take it out like men”: Competitive Masculinity in Novels and Narratives of the Frontier - Vöő, Gabriella (FOCUS: Papers in English Literary and Cultural Studies, 2006)
Last in the order of publication but the first in the chronological order of the plot, James Fenimore Cooper’s The Deers layer (1841) concludes the Leatherstocking series by giving insight into Natty Bumppo’s earliest exploits as a frontier hero. It is the story of the young hunter “just arriving at manhood” (439), stepping on his first warpath. Cooper solidifies, in retrospect, the character of Natty, and puts him through a series of trials before his passage from boyhood to manhood. In a memorable scene of the novel the young Natty Bumppo confronts an experienced Huron warrior, Le Loup Cervier, over the possession of a canoe. Anticipating his opponent’s perfidy, Natty is tempted to fire the first shot before his opponent has the chance to shoot him in the back. However, he finally decides to keep the rules of fair play: “’No-no—that may be red-skin warfare, but it is not a Christian’s gifts. Let the miscreant charge, and then w e’ll take it out like men [. . .]. No, no; let him take time to load, and God will take care of the right!”’ (594, italics added). There is no question as to who God is siding with: in the ensuing exchange of fires Natty triumphs over le Loup Cervier who, with his dying words, gives Deerslayer his man’s name, “Hawkeye” (602), emblematic of his change of status from hunter to warrior. Despite the fact that he was brought up by Indians and had spent his life away from, and in contempt of, “civilized” colonial settlements, Natty gives credit to a notion of manhood that is unarguably white, Christian, and ultimately conforming to Euro-American standards of gentility.